Projeto, construção e proposta de acionamento de um motor linear a relutância chaveado - Domingos, José Luis (2003)
This work is related to modeling, design, construction and driving of a linear switched reluctance motor (LSRM). A mathematical model is derived allowing for the analysis of machine’s motion in the x and z directions. The periodic profile of a stator phase inductance as function of rotor position is represented using Fourier series approach. A set of criteria for designing the motor is discussed and a prototype is designed and built, allowing for experimental verifícation. Measurements of inductance profile, static force profile and magnetization curves as function of position and current is carried out for the built prototype and the results are presented. A four-quadrant drive strategy for motor operation including speed control is proposed and digital simulation is carried out to verify its feasibility. Finally an electronic converter and the associated control strategy are implemented and the realization of experimental verifícation is realized. The experimental results are included in the work and show the suitability of the proposed control strategy.